2018
DOI: 10.1097/meg.0000000000001195
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of hepatitis C with direct-acting antivirals significantly reduces liver-related hospitalizations in patients with cirrhosis

Abstract: Successful DAA treatment reduces hospitalization rate and resource utilization costs in patients with CTP-A and CTP-B, but not in those with CTP-C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…However, they remained largely stable across countries during this period, contrary to modelling studies that have forecasted an increasing burden of liver cirrhosis and other chronic liver diseases [7,16] as well as liver cirrhosis attributable to HCV until 2030 [21,22]. This discrepancy may be due to general improvements in the medical care of patients with cirrhosis over the reporting period, and later on through the impact of direct-acting antivirals (DAA) programmes for HCV patients which have been rolled out in the region and found to be effective in significantly reducing hospitalisations in cirrhotic patients with HCV infection [23]. Liver transplants for which cirrhotic patients would have been hospitalised, have also been stagnant during the reporting period of this study owing to donor shortages [24].…”
Section: Discussionmentioning
confidence: 99%
“…However, they remained largely stable across countries during this period, contrary to modelling studies that have forecasted an increasing burden of liver cirrhosis and other chronic liver diseases [7,16] as well as liver cirrhosis attributable to HCV until 2030 [21,22]. This discrepancy may be due to general improvements in the medical care of patients with cirrhosis over the reporting period, and later on through the impact of direct-acting antivirals (DAA) programmes for HCV patients which have been rolled out in the region and found to be effective in significantly reducing hospitalisations in cirrhotic patients with HCV infection [23]. Liver transplants for which cirrhotic patients would have been hospitalised, have also been stagnant during the reporting period of this study owing to donor shortages [24].…”
Section: Discussionmentioning
confidence: 99%
“…Quality Assessment. SYRCLE's risk of bias tool for animal studies [23] was used for evaluations, including (1) whether the allocation sequence was adequately generated and applied, (2) whether the baselines are identical, (3) whether the allocation adequately concealed, (4) whether the animals were randomized during the experiment, (5) whether the researchers were blinded, (6) whether the animals were selected at random for outcome assessment, (7) whether the result evaluators were blinded, (8) whether incomplete data were reported, (9) whether the research report was irrelevant to the selective results report, and (10) whether there were no other biases. "Yes," "no," and "uncertainty" represent low bias risk, high bias risk, and uncertain bias risk, respectively.…”
Section: Study Selection and Data Extractionmentioning
confidence: 99%
“…Cirrhosis causes approximately 1 million deaths per year [1]. e treatment costs associated with gastrointestinal bleeding, ascites, and other complications are more than three times higher for patients with cirrhosis than for those without cirrhosis [2]. e global burden of liver fibrosis is increasing [3], and drugs to improve liver fibrosis will bring huge benefits.…”
Section: Introductionmentioning
confidence: 99%
“…9 Patients treated with DAAs who achieve SVR have reduced mortality, need for liver transplantation, hepatocellular carcinoma risk, liver-related hospitalizations, and health care costs. 10-14 Risk factors for treatment failure have been described and include advanced liver disease, HCV genotype, hepatocellular carcinoma, and previous DAA treatment failure especially if resistance-associated substitutions are present. 15-21 Failure to achieve SVR has detrimental downstream effects on both clinical outcomes and overall cost of therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, hospitalized patients may experience changes that alter pharmacokinetic elimination and metabolism, with variations in renal and/or hepatic function. A recent study revealed that only 74% of patients with cirrhosis hospitalized for liver-related complications after DAA treatment achieved SVR 13 ; it is important to answer the question if hospitalization during DAA treatment affects or otherwise acts as a prognostic indicator of SVR failure. In addition, identifying patients at risk for hospitalization during treatment may be important to ensure that hospitalized patients have appropriate supply of their DAA regimen during admission.…”
Section: Introductionmentioning
confidence: 99%